2020
DOI: 10.1590/1807-3107bor-2020.vol34.0026
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease and its impact on general health in Latin America. Section V: Treatment of periodontitis

Abstract: Ricardo Guimarães FISCHER (a) Ronaldo LIRA JUNIOR (b) Belén RETAMAL-VALDES (c) Luciene Cristina de FIGUEIREDO (c,d) Zilson MALHEIROS (d,e) Bernal STEWART (d,e) Magda FERES (c,d)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 67 publications
1
59
0
12
Order By: Relevance
“…Non-surgical periodontal treatment can show therapeutic effects in mild to moderate periodontal disease, whereas surgical periodontal therapy is needed in progressive disease conditions [ 10 ]. Supplementary to mechanical debridement in periodontal treatment, various drug delivery methods, mouth rinses, irrigating solutions, and long-term drug release systems are commonly used for therapeutic agent administration [ 10 , 12 ]. Furthermore, routine periodontal therapy combined with an adjunctive therapeutic mediator has been shown to greatly improve patient outcomes as compared to mechanical debridement only [ 10 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Non-surgical periodontal treatment can show therapeutic effects in mild to moderate periodontal disease, whereas surgical periodontal therapy is needed in progressive disease conditions [ 10 ]. Supplementary to mechanical debridement in periodontal treatment, various drug delivery methods, mouth rinses, irrigating solutions, and long-term drug release systems are commonly used for therapeutic agent administration [ 10 , 12 ]. Furthermore, routine periodontal therapy combined with an adjunctive therapeutic mediator has been shown to greatly improve patient outcomes as compared to mechanical debridement only [ 10 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Non-surgical handling can be effective in mild to moderate periodontitis while surgical action is important in progressive conditions [ 10 ]. Adjunctive to the mechanical scaling and root planning in the treatment of periodontal diseases, confined systems of drug delivery, mouth washes, irrigations and devices for sustained drug release are used regularly for conveyance of therapeutic agents [ 10 , 12 ]. Furthermore, it has been reported that regular periodontal treatment along with the use of an adjunctive therapeutic mediator can improve patient outcomes significantly compared to mechanical treatment alone [ 10 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…[24] Periodontitis is an in ammatory disorder raised by the accumulation of speci c bacterial pathogens and the destruction of host immune responses [25]. The clinical ndings of periodontitis included gingival bleeding, tooth mobility, and nally the loss of the tooth, which are associated with a negative impact on Oral Health-Related Quality of Life [26]. Similarities could be discovered between Periodontitis and SSc.…”
Section: Discussionmentioning
confidence: 99%